Stereoselective syntheses of 3-aminocyclooctanetriols and halocyclooctanetriols - Salamci, Emine; Zozik, Yunus (Beilstein Journal of Organic Chemistry, 2021)
The efficient synthesis of two new stereoisomeric 3-aminocyclooctanetriols and their new halocyclitol derivatives starting from cis,cis-1,3-cyclooctadiene are reported. Reduction of cyclooctene endoperoxide, obtained by photooxygenation of cis,cis-1,3-cyclooctadiene, with zinc yielded a cyclooctene diol followed by acetylation of the hydroxy group, which gave dioldiacetate by OsO4/NMO oxidation. The cyclooctane dioldiacetate prepared was converted to the corresponding cyclic sulfate via the formation of a cyclic sulfite in the presence of catalytic RuO4. The reaction of this cyclic sulfate with a nucleophilic azide followed by the reduction of the azide group provided the target, 3-aminocyclooctanetriol. The second key compound, bromotriol, was prepared by epoxidation of the cyclooctenediol with m-chloroperbenzoic acid followed by hydrolysis with HBr(g) in methanol. Treatment of bromotriol with NaN3 and the reduction of the azide group yielded the other desired 3-aminocyclooctanetriol. Hydrolysis of the epoxides with HCl(g) in methanol gave stereospecifically new chlorocyclooctanetriols.
Keywords: aminocyclitols; aminocyclooctanetriol; chlorocyclooctanetriol; cyclic sulfate; cyclitols